FLOW CYTOMETRY AS A MODERN ANALYTICAL TOOL IN BIOLOGY AND MEDICINE - S. V. Khaidukov (SPb RAACI, 2014)
Abstract. Flow cytometry is considered as a modern technology for fast measurements of cellular characteristics, their organelles, and processes occurring within them. It is regarded as an efficient solution in many important areas of cell biology, immunology and cellular engineering. Present article bears on main developments in flow cytometry and their applications in medical and biological practice. Usage of modern achievements in fluorescent dyes, progress in laser and computer technologies, as well as potent software, resulted in wide application of this technique in medical practice. Accordingly, usage of monoclonal antibodies conjugated to different fluorochromes has led to elaboration of multiparametric analysis and did sufficiently simplify specialized works aimed for diagnostics of various immune disorders. The new directions in flow cytometry, e.g., flow cytoenzymology, provide wide opportunities for detailed identification of damaged or altered cells, and taking adequate decisions in treatment of detected pathological changes. The authors suggest that this article could initiate a series of publications concerning usage of this technology and its modern applications in broad laboratory practice.